The US-backed Moroccan- Israeli Normalization Agreement: Implications on the Future of the Maghreb Union - Guemide, Boutkhil; Amir, Samir (The Journal of US-Africa Studies, 2021)
After the signing of the Abraham Accords between the Zionist entity and the countries of the United Arab Emirates (UAE) and Bahrain under the auspices of US President Trump, Morocco joined the normalization process and became the latest country in the Arab League which agreed to normalize its relations with Israel through US mediation. As part of the agreement, the US agreed to recognize Morocco’s sovereignty over the disputed Western Sahara region, and to release 1 billion in military aid to Morocco. This Moroccan step added fuel to the flame and worsened its relations with the Palestinian Authority, on the one hand, and the countries of the Maghreb union, on the other hand. Morocco’s normalization of its relations with the Zionist entity does not only deteriorate its relations with Algeria, which supports the POLISARIO, but also affects the future of the Maghreb union. This paper discusses the implications of Morocco’s normalization of its relations with the Zionist entity on the Arab Maghreb integration project. It takes into account the Moroccan normalization process as a part of the overall Arab approach. In addition, it highlights the Israeli relations with the Maghreb countries of Morocco, Mauritania, and Tunisia, and how Moroccan normalization will affect the future of integration of Maghreb union. Key words: Morocco; Israel; Normalization; Maghreb Union; Algeria.